Advances in computational intelligence and autonomy for aerospace systems - Valasek, John; Lieuwen, Timothy C.; Valasek, John (American Institute of Aeronautics and Astronautics, Inc., 2018)
"A follow-on volume to Advances in Intelligent and Autonomous Aerospace Systems (AIAA, 2012), Advances in Computational Intelligence and Autonomy for Aerospace Systems seeks tp provide both the aerospace researcher and the practicing aerospace engineer with further insight into the latest innovative methods and approaches regarding intelligent and autonomous aerospace systems."--Page 4 of cover
Series editor-in-chief: Timothy C. Lieuwen, Georgia Institute of Technology.
Keywords: Aerospace engineering -- Technological innovations.; Intelligent control systems.; Artificial intelligence.; Artificial immune systems -- Effect of space flight on.; Aeronautics -- Systems engineering.; Space vehicles -- Control systems -- Design and construction.; elektronické knihy; electronic books